Heartfulness meditation improves sleep in chronic insomnia. Issue 1 (2nd January 2020) - Thimmapuram, Jayaram; Yommer, Deborah; Tudor, Luminita; Bell, Theodore; Dumitrescu, Cristian; Davis, Robert
ABSTRACT: Background: Chronic insomnia is characterized by disturbed sleep that occurs despite adequate opportunity and circumstances to sleep. Many patients with chronic insomnia have comorbid mental illnesses or medical illnesses that contribute and precipitate insomnia. Hallmark of chronic insomnia treatment includes non-pharmacological measures such as Cognitive Behavioral Therapy for Insomnia (CBT-I). Pharmacologic treatment (sedative or hypnotic agents) has been disappointing because of poor efficacy and numerous undesirable side effects. Other new therapies including meditation have been proven to be effective. Objective: This study investigates the effectiveness of Heartfulness meditation coupled with sleep hygiene to treat chronic insomnia. Methods : In this prospective pre-post design cohort study, 32 adult patients with chronic primary insomnia engaged in Heartfulness meditation along with appropriate sleep hygiene for eight weeks. Insomnia Severity Index (ISI) scores, usage of sedative or hypnotic agents were measured at baseline and at the end of the eight-week period. Results: There was a significant decrease in the mean ISI scores from 20.9 to 10.4 (p < 0.001) after eight weeks of Heartfulness meditation. Twenty four of 32 patients were initially on sedative or hypnotic medications. At week eight, 21 of 24 patients (87.5%) were off these medications or the dosage was reduced (p < 0.001). Conclusion: This study demonstrated statistical improvements in the measures of ISI in patients undergoing a Heartfulness meditation program. Heartfulness meditation may facilitate the taper and eventual cessation of sedative hypnotics in patients suffering from chronic insomnia.